ANALISA RATIO LIKUIDITAS, SOLVABILITAS DAN PROFITABILITAS PADA PT. SEMEN BATURAJA PALEMBANG TAHUN 2012-2013 - Harsi Romli; Rezky Ferita; Lukita Tri Permata (Jurnal Ilmiah Ekonomi Global Masa Kini)
The purpose of this research is to analyze the financial performance of PT. Semen Baturaja Palembang based on the result of analysis of financial ratios on the financial statements of each company during the period 2012-2013 in terms of liquidity ratios, solvency ratios, and profitability ratios.Secondary data sources that author use is based on PT. Semen Baturaja Palembang in the form of financial statements of each company during the period 2012 to 2013. Data analysis that used in this study consisted of liquidity ratios, solvency ratios, and profitability ratios.Based on research results of the data in the financial statements of PT. Semen Baturaja Palembang, the company’s liquidity ratio above 200%. While the solvency ratio, the state of the company at a solvable. Because of the company’s capital in sufficient quantities to secure the loan granted by creditors. The profitability ratio of PT. Semen Baturaja Palembang is good enough to produce a profit every year.Keywords: Financial Performance, Liquidity Ratio, Solvency Ratio, and Profitability Ratio